2018
DOI: 10.1016/j.jtho.2018.08.530
|View full text |Cite
|
Sign up to set email alerts
|

MA25.02 Searching for a Definition of Synchronous Oligometastatic (sOMD)-NSCLC: A Consensus from Thoracic Oncology Experts

Abstract: physicians confirmed sOMD patients with brain MRI (91%, n¼403) and PET-CT (98%, n¼437). For mediastinum staging, most (64%, n¼285) respondents stated that histology/cytology should be obtained when PET-CT shows suspected lymph nodes or in case of a central primary tumor. Pathology proof of metastatic disease was necessary in sOMD for 315 (71%) physicians, and 37% (n¼163) acknowledged that histology should be obtained from at least from one metastatic site. Preferred primary outcome parameter in clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…5,6 In an attempt to provide a definition of sOM NSCLC, the European Organization for Research and Treatment of Cancer (EORTC) Lung Cancer Group (LCG) developed a consensus definition based on clinical cases of sOM disease, a European survey on sOM disease, and a systematic review of the currently requested staging methods and definitions of the term synchronous oligometastatic used in clinical trials. [7][8][9] Here we report the results of the systematic review.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In an attempt to provide a definition of sOM NSCLC, the European Organization for Research and Treatment of Cancer (EORTC) Lung Cancer Group (LCG) developed a consensus definition based on clinical cases of sOM disease, a European survey on sOM disease, and a systematic review of the currently requested staging methods and definitions of the term synchronous oligometastatic used in clinical trials. [7][8][9] Here we report the results of the systematic review.…”
Section: Introductionmentioning
confidence: 99%
“…However, to be able to design and compare trials, a single definition is needed. The EORTC oligometastatic definition group has formulated a consensus statement on the definition of synchronous oligometastatic NSCLC [16]. This definition should be prospectively tested in future randomised trials and in the EORTC-ESTRO (European Society for Therapeutic Radiation and Oncology) OligoCare project (a pragmatic observational basket study to evaluate radical radiotherapy for oligometastatic cancer patients).…”
Section: Discussionmentioning
confidence: 99%
“…Only for one trial, overall survival (OS) results have been reported, with a median OS of 41.2 months for the LRT arm and 17 months for the control arm [15]. The inclusion criteria such as the number of metastases, considering the primary and/or mediastinal lymph nodes, eligibility of patients with driver mutations and treatment sequence varied (Table 1) [16].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to come to a consensus definition, which would aid the development of clinical trials, the European Organization for Research and Treatment of Cancer (EORTC) Lung Cancer Group organized a consensus meeting (13). It was proposed that oligometastases are defined as a maximum of five metastases and three organs.…”
Section: Definition Of Oligometastasesmentioning
confidence: 99%